It goes on: Oil Palm Plantations, Local Communities and Land Conflict in West Pasaman District, Indonesia - Indrizal, Edi; Ermayanti, Ermayanti; Irwandi, Ade; Anwar, Hairul; Alyan, Rizka Ananda (JURNAL SOSIAL HUMANIORA (JSH), 2024)
This research seeks to elucidate the conflict over PT PHP I's Cultivation Rights Title (HGU), claimed as customary land by some communities in Nagari Kapa. It aims to detail the customary elements that legitimized the 1997 land rights transfer to the West Pasaman Regency government. The issue stems from internal conflicts among Nagari Kapa's customary elites, impacting PT PHP I as the HGU holder. The disputed area encompasses 315 hectares of PT PHP I's land, occupied by the community since 2020. Using ethnographic methods, the study explores community and tribal leaders' (Ninik Mamak) perspectives on customs and land status. Interviews were conducted with 10 groups of tenant farmers on PT PHP I's core HGU land and 5 Ninik Mamak. Findings reveal that land status, under the Babingkah Adat system, is determined by the Pucuk Adat and transferred according to Adat Diisi Limbago Dituang and Siliah Jariah customary requirements. However, some community members oppose this mechanism, occupying land designated as PT PHP I's HGU, and thus, they collectively claim the land as customary territory of the Nagari Kapa community.